1999
DOI: 10.1042/cs19980275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ursodeoxycholic acid on systemic, renal and forearm haemodynamics and sodium homoeostasis in cirrhotic patients with refractory ascites

Abstract: Systemic arterial vasodilatation has been implicated in the pathogenesis of sodium retention in cirrhosis. Hydrophobic bile acids, which have vasodilatory actions, may be involved. Ursodeoxycholic acid, a hydrophilic bile acid, could potentially decrease systemic arterial vasodilatation, possibly due to its antioxidant effects, and improve sodium handling in cirrhosis. The effects of ursodeoxycholic acid on systemic, renal and forearm haemodynamics, liver function and renal sodium handling were assessed in vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This resulted in a slight but insignificant reduction in MAP, similar to recent findings from cirrhotic patients [14]. The decrease in DBP was not related to any impairment in the function of the myocardium or the sino-atrial node, as previously described for hydrophobic bile acids [15, 16].…”
Section: Discussionsupporting
confidence: 72%
“…This resulted in a slight but insignificant reduction in MAP, similar to recent findings from cirrhotic patients [14]. The decrease in DBP was not related to any impairment in the function of the myocardium or the sino-atrial node, as previously described for hydrophobic bile acids [15, 16].…”
Section: Discussionsupporting
confidence: 72%
“…There was no change in these systemic haemodynamic parameters, heart rate or mean arterial pressure during or after the end of the treatment, but the authors noted a decrease in sodium clearance and weight gain in all patients, concluding that UDCA led to sodium retention. 88 More recent studies have yielded similarly conflicting results. Thus, Schiedermaier et al 89 reported a decrease in diastolic blood pressure but not portal flow in a small human cross-over study, while Yang et al 90 described a reduction in portal pressure due to diminished intrahepatic resistance in a rat model.…”
Section: Lessons Learnt From Therapy: Ursodeoxycholic Acid and Obetmentioning
confidence: 99%
“…In fact, studies on the effects of chronic administration of UDCA on systemic haemodynamics are still limited. In healthy volunteers, 4 weeks of UDCA (750 mg/day) treatment induced a slight decrease in MAP [51]; however, MAP, heart rate, cardiac output and systemic vascular resistance were not changed by treatment for 1 month with UDCA (15 mg · kg −1 of body weight · day −1 ) in patients with cirrhosis and refractory ascites [20]. In our present study, treatment for 1 month with UDCA (50 mg · kg −1 of body weight · day −1 ) also did not change mesenteric blood flow and MAP in BDL rats.…”
Section: Figure 6 Representative Histology Sections Of Livers From Bdmentioning
confidence: 93%
“…Some peripheral effects of chronic UDCA treatment have been reported in cirrhosis [18][19][20]; however, the effects of UDCA in cirrhotic livers are still unclear. Therefore the aim of the present study was to investigate the effects of chronic UDCA administration in the livers of rats with biliary cirrhosis.…”
Section: Introductionmentioning
confidence: 99%